Pelatihan Literasi Kesehatan Digital Bagi Kader Posyandu Untuk Deteksi Dini Penyakit Hipertensi Di Desa Kunduran Kecamatan Ulu Musi Kabupaten Empat Lawang - Hengki Tranado; Saputra , Fery Surahman; Juita, Rina; Habibi , Julius; Hidayat , Yance (Jurnal Semarak Mengabdi, 2026)
Hypertension is a non-communicable disease whose prevalence continues to increase globally and nationally. According to the World Health Organization (WHO), hypertension is a condition where systolic blood pressure reaches ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. It is known as a silent killer because it often has no symptoms in its early stages. According to the World Health Organization (WHO), by 2024, an estimated 1.4 billion adults aged 30–79 worldwide will suffer from hypertension, representing approximately 33% of the population in that age range. Based on the 2023 Indonesian Health Survey (SKI), the prevalence of hypertension among people aged 18 years and over reached 30.8%, indicating that nearly one-third of adults live with high blood pressure. According to the "2023 Profile" from the Empat Lawang Regency Health Office, data from 2023 indicates that in Empat Lawang Regency, there are an estimated 52,374 residents aged 15 years and over with hypertension. Of this number, 28,164 hypertension sufferers received healthcare services. According to the data, approximately 53.8% of the estimated hypertension sufferers in Empat Lawang received healthcare. According to data from the Padang Tepong Community Health Center (Puskesmas), in 2024, there were 80 hypertension cases. The number of Posyandu (Integrated Health Post) cadres at the Padang Tepong Community Health Center was 70. There were 5 Posyandu cadres in Kunduran village. Digital health literacy training for Posyandu cadres can be theoretically justified through the concept of eHealth literacy, which is the ability to search for, find, understand, and evaluate health information from electronic sources, and apply that knowledge to solve health problems. This literacy is crucial in the digital era because much health information is now available online, and access alone is insufficient without the ability to assess the quality of sources and the relevance of the information. Therefore, digital health literacy training for Posyandu cadres for early detection of hypertension in Kunduran village, Ulu Musi District, Empat Lawang Regency, is crucial to strengthening early detection efforts.